Why does the Chinese public accept evolution?. (June 2020) - Zhu, Jing; Zhang, Mingjun; Weisberg, Michael
Abstract: A substantial proportion of Chinese nationals seem to accept evolution, and the country is sometimes held up to show that the sorry state of evolution acceptance in the United States is not inevitable. Attempts to improve evolution acceptance generally focus on improving communication, curricular reform, and even identifying cognitive mechanisms that bias people against evolution. What is it that the Chinese scientific community did so well, and can it be generalized? This paper argues that evolution acceptance in China has a very specific history, one that other countries are very unlikely to emulate. We show that the interactions among science, education, mass media, social and political movements, and ideological arguments about evolution greatly influenced the Chinese public's understanding and acceptance of evolution. We find that it was not just formal education, but many more ideologically motivated methods of evolution exposure that contributed to the high rate of acceptance. But since the purpose of evolution dissemination has moved beyond merely teaching biology, the Chinese public persists with substantial misunderstandings of the theory. Thus, bottom line percentage of acceptance figures can be misleading; the details and the history really matter. Highlights: The Chinese public accepts evolution at a very high rate because of the social history of evolutionary concepts in China. Multiple ways of continuous and intensive evolution dissemination had exposed the entire country to the idea of evolution. Evolutionary thinking in China has traditionally been deeply political, which shapes the public's understanding of evolution today.